Ligation-independent cloning of PCR products (LIC-PCR). - Aslanidis, C (1990)
A new procedure has been developed for the efficient cloning of complex PCR mixtures, resulting in libraries exclusively consisting of recombinant clones. Recombinants are generated between PCR products and a PCR-amplified plasmid vector. The procedure does not require the use of restriction enzymes, T4 DNA ligase or alkaline phosphatase. The 5'-ends of the primers used to generate the cloneable PCR fragments contain an additional 12 nucleotide (nt) sequence lacking dCMP. As a result, the amplification products include 12-nt sequences lacking dGMP at their 3'-ends. The 3'-terminal sequence can be removed by the action of the (3'----5') exonuclease activity of T4 DNA polymerase in the presence of dGTP, leading to fragments with 5'-extending single-stranded (ss) tails of a defined sequence and length. Similarly, the entire plasmid vector is amplified with primers homologous to sequences in the multiple cloning site. The vector oligos have additional 12-nt tails complementary to the tails used for fragment amplification, permitting the creation of ss-ends with T4 DNA polymerase in the presence of dCTP. Circularization can occur between vector molecules and PCR fragments as mediated by the 12-nt cohesive ends, but not in mixtures lacking insert fragments. The resulting circular recombinant molecules do not require in vitro ligation for efficient bacterial transformation. We have applied the procedure for the cloning of inter-ALU fragments from hybrid cell-lines and human cosmid clones.